(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
This paper shows a method to deepen the knowledge about the rapid solidification of metal alloy powders via in-situ investigation and to guide the proper parameter selection for rapid solidification process methods, e.g. laser or electron beam melting in additive manufacturing (AM). This allows developing microstructure maps to establish regimes of alloy composition and undercooling required for design of materials with improved mechanical properties. Differential fast scanning calorimetry (DFSC) characterization and microstructure analysis carried out on the example of Al-Si alloys, as important engineering materials often used in AM, will improve understanding of rapid solidification processes and microstructure formation.